1998
DOI: 10.1542/peds.101.5.926
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline-induced Lupus in Adolescents

Abstract: 9. Golstein PE, Deviere J, Cremer M. Acute hepatitis and drug-related lupus induced by minocycline treatment. Am J Gastroenterol. 1997;92:143-146. 10. Singer SJ, Piazza-Hepp TD, Girardi LS, Moledina NR. Lupuslike reaction associated with minocycline. JAMA. 1997;277:295-296. 11. Crosson J, Stillman MT. Minocycline-related lupus erythematosus with associated liver disease. J Am Acad Dermatol. 1997;36(5 More than 44000 new cases of melanoma are detected annually in the United States, and the number is stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Initial studies emphasized its relative safety and identified common adverse effects including headache, lightheadedness, vertigo, nausea, weakness, and rash. [1][2][3] As its use has increased, more serious sequelae have been identified, including serum sickness-like reaction, drug-induced lupus, 4 pneumonitis, hypersensitivity syndrome reaction, acute febrile neutrophilic dermatosis (Sweet disease), and hepatitis. 5 We describe 3 adolescents in whom autoimmune hepatitis developed related to minocycline use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies emphasized its relative safety and identified common adverse effects including headache, lightheadedness, vertigo, nausea, weakness, and rash. [1][2][3] As its use has increased, more serious sequelae have been identified, including serum sickness-like reaction, drug-induced lupus, 4 pneumonitis, hypersensitivity syndrome reaction, acute febrile neutrophilic dermatosis (Sweet disease), and hepatitis. 5 We describe 3 adolescents in whom autoimmune hepatitis developed related to minocycline use.…”
Section: Discussionmentioning
confidence: 99%
“…Others who responded to withdrawal of the drug alone may be reacting to an antigen that bears similarity to an autoantigen. Whether the minocycline is responsible for the autoimmune hepatitis in this large population of adolescents exposed to the drug is difficult to determine; causation is supported by the number of reports linking the two, 5,6,[8][9][10][11][12] the association of minocycline with other autoimmune diseases like lupus, 4,5,12 and the resolution of symptoms in the majority of affected patients when the drug is withdrawn.…”
mentioning
confidence: 99%
“…Clinical symptoms are similar to those of SLE in that arthralgia, arthritis, myalgia, fever, and malaise are often present. 1,23,34,41,[45][46][47] Drug-induced lupus differs from SLE in that there is less of a discrepancy in the male-female ratio, skin involvement is dependent on the specific medication in DIL but is generally less common than in SLE, and renal involvement is comparatively less frequent in DIL than in SLE. 41 Testing positive for ANAs is a common finding in SLE and in DIL.…”
Section: Drug-induced Lupusmentioning
confidence: 99%
“…However, testing positive for antibodies to doublestranded DNA is common in SLE but is rare in DIL. 1,34,41 In SLE, the ANAs and the antibodies to double-stranded DNA are theorized to bond with their common antigen, resulting in immune complexes that are deposited in the skin (in the case of discoid lupus erythematosus) or in vascular tissues throughout the body t study desiGn: Resident's case problem. t bAckGRound: In the United States, minocycline is a frequently prescribed medication for the treatment of moderate to severe acne, a common condition in adolescents.…”
Section: Drug-induced Lupusmentioning
confidence: 99%
See 1 more Smart Citation